The expression of Müllerian inhibiting substance/anti-Müllerian hormone type II receptor in myoma and adenomyosis - Shin Young Kim; Hye Min Moon; Min Kyoung Lee; Youn Jee Chung; Jae Yen Song; Hyun Hee Cho; Mee Ran Kim; Jang Heub Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveWe compared the expression levels of Müllerian inhibiting substance (MIS)/anti-Müllerian hormone type II receptor (AMHRII) in uterine myoma and adenomyosis to evaluate the possibility of using MIS/anti-Müllerian hormone (AMH) as a biological regulator or therapeutic agent in patients with uterine leiomyoma and adenomyosis.MethodsWe studied normal uterine myometrium, leiomyoma, endometrial tissue, and adenomyosis from 57 patients who underwent hysterectomy for uterine leiomyoma (22 cases) or adenomyosis (28 cases) and myomectomy for uterine myoma (7 cases). Immunohistochemical staining was used to confirm the MIS/AMHRII protein expression level in each tissue. Reverse transcription-polymerase chain reaction was performed to quantify MIS/AMHRII mRNA expression.ResultsThe MIS/AMHRII protein was more strongly expressed in uterine myoma (frequency of MIS/AMHRII expressing cells: 51.95%±13.96%) and adenomyosis (64.65%±4.85%) tissues than that in the normal uterine myometrium (3.15%±1.69%) and endometrium (31.10%±7.19%). In the quantitative analysis of MIS/AMHRII mRNA expression, MIS/AMHRII mRNA expression levels in uterine myoma (mean density: 4.51±0.26) and adenomyosis (6.84±0.20) tissues were higher than that in normal uterine myometrial tissue (0.08±0.09) and endometrial tissue (1.63±0.06).ConclusionThis study demonstrated that MIS/AMHRII was highly and strongly expressed on uterine myoma and adenomyosis. Our data suggest that MIS/AMH may be evaluated as a biological modulator or therapeutic agent on MIS/AMHRII expressing uterine myoma and adenomyosis.